2006
DOI: 10.1016/j.febslet.2006.10.055
|View full text |Cite
|
Sign up to set email alerts
|

The role of cystatins in cells of the immune system

Abstract: The cystatins constitute a large group of evolutionary related proteins with diverse biological activities. Initially, they were characterized as inhibitors of lysosomal cysteine proteases -cathepsins. Cathepsins are involved in processing and presentation of antigens, as well as several pathological conditions such as inflammation and cancer. Recently, alternative functions of cystatins have been proposed: they also induce tumour necrosis factor and interleukin 10 synthesis and stimulate nitric oxide producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 87 publications
(98 reference statements)
4
88
0
1
Order By: Relevance
“…However, our data indicate that FheCL1 is resistant to this proteolytic degradation, which is consistent with our earlier findings showing that the mature enzyme is highly resistant to proteolytic degradation by endopeptidases (33). We have also shown that FheCL1 can degrade cystatins/serpins such as SCCA1 and SCCA2 (34) and therefore this may protect the enzyme from inhibition by cystatins within the lysosome that are known to regulate the activity of resident endolysosomal cathepsins (35).…”
Section: Discussionsupporting
confidence: 92%
“…However, our data indicate that FheCL1 is resistant to this proteolytic degradation, which is consistent with our earlier findings showing that the mature enzyme is highly resistant to proteolytic degradation by endopeptidases (33). We have also shown that FheCL1 can degrade cystatins/serpins such as SCCA1 and SCCA2 (34) and therefore this may protect the enzyme from inhibition by cystatins within the lysosome that are known to regulate the activity of resident endolysosomal cathepsins (35).…”
Section: Discussionsupporting
confidence: 92%
“…Cathepsins are involved in processing and presentation of antigens, and are also involved in several pathological conditions such as inflammation and cancer. Cystatins can also induce synthesis of tumor necrosis factor and interleukin 10, and stimulate nitric oxide production (17).…”
Section: Discussionmentioning
confidence: 99%
“…The cystatins are naturally occurring cysteine proteinase inhibitors (see Kopitar-Jerala, 2006). We identified and cloned a cystatin from S. domuncula.…”
Section: Discussionmentioning
confidence: 99%
“…the cystatins and the stefins [see http://merops.sanger.ac.uk (Rawlings et al, 2004)]. These molecules are subdivided into (i) type 1 cystatins, cystatin/stefins A and B; these are polypeptides of ~98 amino acid residues that possess neither disulphide bonds nor carbohydrate side chains, and are located mainly intracellularly; (ii) type 2 cystatins C, D, E/M, F, S, SN, and SA; these are characterized by conserved disulphide bridges; and (iii) type 3 cystatins, the kininogens (Kopitar-Jerala, 2006). For the analysis of the proteinase specificity in the sponge spicules, type 1 sponge cystatin was cloned and the recombinant protein prepared.…”
Section: Sponge Cysteine Proteinase Inhibitor: Cystatinmentioning
confidence: 99%